A nanoscale interlayer void design enabling high-performance SnO2-carbon anodes. (15th October 2021) - Li, Yudong; Lin, Kui; Qin, Xianying; Zeng, Kun; Liu, Yushan; Xia, Yue; Lv, Fengzheng; Zhu, Hua; Kang, Feiyu; Li, Baohua
Abstract: SnO2 is considered as a promising anode material for lithium-ion batteries (LIBs) in view of its high theoretical capacity. However, the large volume change and low reversible capacity of SnO2 anode have restricted its practical application. In this study, the two issues were overcome by fabricating SnO2 -carbon composite with an optimized structure: SnO2 /carbon nanoclusters, composed of ultrafine SnO2 nanocrystals and carbon boundary, with well-defined interlayer void space were monodispersed encapsulated in graphene-supported carbon framework (denoted SCVC composite). The nanoscale interlayer gap could buffer volume expansion of SnO2 . The numerous carbonaceous boundaries between ultrafine SnO2 nanocrystals could prevent Sn/Lix Sn coarsening, guaranteeing sufficient Sn/Li2 O interdiffusion and enhancing conversion fraction of Sn and Li2 O to SnO2 during charging. While the graphene-based carbon framework would enable a fast ion/electron transport and stable solid electrolyte interface. As a result, the SCVC-based LIBs delivered a high reversible capacity, ultralong cycling life-span and excellent rate capability. A capacity of 643 mAh g −1 at 5 A g −1 was retained after 1000 cycles for the SCVC anode. A high reversible capacity accessibility of 1239 mAh g −1 could be reached at 0.5 A g −1 for the SnO2 component in SCVC anode. Graphical abstract: Image 1